(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Eight-and-a-Half-syndrome is a rare clinical manifestation of stroke, where involvement of ocular motor movement manifested by horizontal gaze palsy to one direction, internuclearophthalmoplegia in the other and ipsilateral lower motor neuron seventh cranial nerve palsy. We report a case of eight-a-half syndrome. A 55 years old female known to have Type 2 Diabetes Mellitus, ischemic heart disease presented with double vision, dizziness, deviation of the mouth to the right for 2 days. Her vision was normal, no symptoms of raised intracranial pressure, no limb weakness, slurring of speech. At presentation, patient had poorly controlled diabetes. There were left eye limitation in abduction with contralateral right abducting eye nystagmus, left eye limited abduction consistent with right one and half syndrome. There was also left lower motor neuron facial nerve (7th) palsy. Eight -and-a-half syndrome is a combination of ipsilateral one-and-half syndrome and lower motor neuron facial(7th) nerve palsy. Brainstem conjugate gaze palsy is an important clinical finding, help in diagnosis even a small pontine lesion. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 38-40